Elaboração e validação de conteúdo de um catálogo de meios de treinamento para a prova de 5.000m de atletismo - Anderson Ferreira Gonçalves (2022)
Training planning is an important step in the pursuit of sporting success. As important as the empirical evidence diagnosed by the coach in the training prescription is, the theoretical foundation coming from scientific research in the different areas related to sports science is increasingly necessary. The PRACTE model proposes the creation of a guideline of training means for each sport modality, which should be elaborated by experienced coaches in the modality and scientifically validated. The objective of this work was to elaborate and validate the content of a catalog of training means for the 5,000m athletics events. The guideline was prepared in three stages. Initially, a systematic review was carried out, followed by interviews with experts. The training means elaborated in the two stages were organized and gave rise to the guideline. This guideline was evaluated by judges and experts regarding Clarity of Language, Practical Pertinence, Theoretical Relevance and specificity. 66 means of training were prepared, classified into 15 categories according to their purposes. Nine training means were classified as general, 22 as special and 35 as specific.